Engaging hospitals to meet tuberculosis control targets in China: using the Internet as a tool to put policy into practice - Lixia Wang; Xiaoqiu Liu; Fei Huang; Cornelia Hennig; Mukund Uplekar; Shiwen Jiang
Tuberculosis (TB) services in China are provided through a large network of TB dispensaries. Even though hospitals are not as well placed to follow recommended standards of TB care, a significant proportion of people with TB symptoms seek care from hospitals. In spite of having a policy and mandate in place, the Ministry of Health had little success in encouraging hospitals to refer suspected TB cases to dispensaries. Following the epidemic of severe acute respiratory syndrome in 2003, the government set up a nationwide Internet-based communicable diseases reporting system. This achieved productive collaboration between hospitals and TB dispensaries. From 2004 to 2007, the percentage of TB suspects and patients needing referral from hospitals who arrived in TB dispensaries increased substantially from 58.7% to 77.8% and the contribution of hospitals to diagnosing sputum smear-positive TB cases doubled from 16.3% to 32.9%. Using the Internet-based reporting system, hospitals in China contributed to finding about one third of all sputu m smear-positive TB cases and helped meet the global TB control target of detecting 70% of such cases. Based on the data available from routine surveillance facilitated by this Internet-based system, this paper details the process and outcomes of strengthening collaboration between hospitals and TB dispensaries using the Internet as a tool and its potential application to other country settings.